Serous effusions in Burkitt lymphomas: a report of two paediatric cases with review of literature - Kumar, Mayank; Rao, Meenakshi; Khera, Sudeep; Sinha, Arvind; Nalwa, Aasma (International Journal of Research in Medical Sciences, 2022)
The serosal cavity can be involved in many diseases, both benign and malignant. Such involvement is secondary to occurrence of disease at other sites. Lymphoma, although not a very common cause for serous effusion, is one of the most important one. The reason for serosal involvement in lymphomas has not been fully elucidated. These two cases highlight the importance of pleural and peritoneal fluid examination in the diagnosis of lymphoma. There is correlation between fluid examination and subsequent cytological and histopathological studies, with immunohistochemical confirmation. A comprehensive understanding of the mechanism of serosal involvement in lymphomas may lead to early diagnosis, better patient management and also development of newer treatment modalities for the same.